(untitled) (Journal of Nepal Geological Society, 1982)
River terraces along the middle Kali Gandaki and the Marsyandi Khola are all fill (filltop and fillstrath) terraces, and no strath (rock) terraces are distributed. Three valley-fill deposits are disinguished along the Kali Gandaki and two along the Marsyandi, and some of them are not normal fluvial deposits but mudflow ones in origin. The formative process of terraces along each river was strongly controlled by local and accidental geomorphic events, besides climatic change and other regional factors. Therefore the correlation of terraces between both rivers is very confused. Based on the longitudinal profiles of terraces, the tectonic movement along the middle Kali Gandaki is inferred that the region around Phalebas relatively subsided and the northern and southern regions were comparatively uplifted during the late Quaternary.